Happy Family Kitchen II: a cluster randomized controlled trial of a community-based positive psychology family intervention for subjective happiness and health-related quality of life in Hong Kong. Issue 1 (December 2016) - Ho, Henry; Mui, Moses; Wan, Alice; Ng, Yin-lam; Stewart, Sunita; Yew, Carol; Lam, Tai; Chan, Sophia
Abstract Background Most positive psychology interventions conducted in the West have been focused on the individual. Family relationships are highly valued in the Chinese collectivist culture, and it is of interest to know whether family-focused interventions can improve the well-being of Chinese people. We have previously reported the effectiveness of a positive psychology family intervention in terms of family well-being. Based on the data derived from the Happy Family Kitchen II project, this paper examines the effectiveness of a community-based positive psychology family intervention on subjective happiness and health-related quality of life. Methods Thirty-one social service units and schools organized intervention programs for 2070 participants in Hong Kong. In a cluster randomized controlled trial, participants were randomly assigned on the basis of computer-generated numbers into the intervention group or the control group. The intervention programs emphasized one of five positive psychology themes: joy, gratitude, flow, savoring, and listening. The control group engaged in activities unrelated to the intervention, such as arts and crafts workshops. Subjective happiness and mental and physical quality of life were assessed at baseline and at 4 weeks and 12 weeks postintervention. Results Data of 1261 participants were analyzed. The results showed that the intervention was more effective than the control condition in improving subjective happiness, with a small effect size, at 12 weeks postintervention (β = .15, p = .020, Cohen'sd = .16). However, there were no improvements in mental and physical quality of life in the intervention group compared with the control group at 4 weeks (β = .39, p = .494, d = .05; β = −.10, p = 1.000, d = −.01, respectively) and 12 weeks postintervention (β = .71, p = .233, d = .08; β = −.05, p = 1.000, d = −.01, respectively). Furthermore, the booster session was no more effective than the tea gathering session in improving subjective happiness (β = .00, p = .990, d = .00) or mental (β = 1.20, p = 1.000, d = −.04) and physical quality of life (β = .15, p = 1.000, d = −.01). Conclusions The analyses extend previous findings of salutary effects on family well-being by showing that positive psychology family interventions can improve subjective happiness. Suggestions for future research are proposed. Trial registration ClinicalTrials.govNCT01796275 . Retrospectively registered 19 February 2013.